In-season whole-body vibration training enhances vertical jump performance in professional soccer goalkeepers - Hawkey, A.; Morrison, D. (Turkish Journal of Sport and Exercise, 2017)
Goalkeepers play an important role in soccer, often influencing match outcome. Soccer goalkeepers have superior jumping ability compared with their outfield counterparts and research has highlighted the importance of this ability. While there is evidence that whole body vibration training (WBVT) can improve explosive power in various populations, there is no data focusing on how this training modality may benefit soccer goalkeepers. With institutional ethics approval, 20 professional male soccer goalkeepers (age = 24 ± 6 yrs.; mass = 84 ± 10.3 kg; height = 1.84 ± 0.1 m) from the English Football League Division One were randomly assigned to either a WBVT or control group. The WBVT group performed static squats from their individual ready position, which is utilised by goalkeepers prior to performing any dynamic movements, on a vibration platform twice-a-week over a five-week period. The control group followed the same exercise programme without the application of vibration. Vertical jump performance, initiated from the goalkeepers` individual ready position, was measured prior to, and on completion of, the five-week study. A 2-way ANOVA with repeated measures showed an improvement in the experimental group`s jump performance from 49.2 ± 4.4 cm pre-training to 53.8 ± 3.5 cm post-training, while the control group`s performance remained stable from 47.02 ± 4.8 cm pre-training to 46.6 ± 4.5 cm post-training, resulting in a significant time-by-group interaction (P<0.001). Findings of the current study provide evidence supporting WBVT`s incorporation into goalkeepers` training regimes.